A meta-analysis to determine the effect on survival of platelet transfusions in patients with either spontaneous or traumatic antiplatelet medication-associated intracranial haemorrhage. Issue 2 (5th April 2012) - Batchelor, John S; Grayson, Alan
Abstract : Objectives: The aim of this study was to evaluate by meta-analysis the current level of evidence in order to establish the impact of a platelet transfusion on survival in patients on pre-injury antiplatelet agents who sustain an intracranial haemorrhage (either spontaneous or traumatic). Design: This was a meta-analysis; the MEDLINE Database was searched using the PubMed interface and the Ovid interface. CINAHL and EMBASE Databases were also searched. The search was performed to identify randomised controlled trials (RCT)'s case-controlled studies or nested case-controlled studies. Comparing the outcome (death or survival) of patients with intracranial haemorrhage (ICH) and pre-injury antiplatelet agents who received a platelet transfusion against a similar cohort of patients who did not receive a platelet transfusion. Results: 499 citations were obtained from the PubMed search. 31 full articles were reviewed from 34 abstracts. 6 studies were found suitable for the meta-analysis. No randomised controlled studies were identified. 2 of the six studies were in patients with spontaneous ICH. The remaining four studies were in patients with traumatic intracranial haemorrhage. Significant heterogeneity was present between the studies, I 2 =58.276. The random effects model was therefore the preferred model, this produced a pooled OR for survival of 0.773 (95% CI 0.414 to 1.442). Conclusions: The results of this meta-analysis has shown, based upon six small studies, that there was no clear benefit in terms of survival in the administration of a platelet transfusion to patients with antiplatelet-associated ICH. Further work is required in order to establish any potential benefit in the administration of a platelet transfusion in patients with spontaneous or traumatic intracranial haemorrhage who were on pre-injury antiplatelet agents.